A Novel Prognostic Nomogram for Patients With Recurrence of Intrahepatic Cholangiocarcinoma After Initial Surgery - Xing, Kai-Li; Lu, Liang-He; Huang, Xin; He, Chao-Bin; Song, Yun-Da; Guo, Rong-Ping; Li, Sheng-Ping (Frontiers in Oncology, 2020)
Background: Data on the outcomes of patients with recurrent intrahepatic cholangiocarcinoma (ICC) after initial resection are limited. This study aimed to establish and validate a nomogram to predict individual post-recurrence survival (PRS) for recurrent ICC patients. Methods: From 2000 to 2016, a total of 237 postoperative recurrent ICC patients were enrolled in this study and randomly divided into training (n=178) and validation cohorts (n=59) at a ratio of 3:1. The predictive accuracy and discriminative ability of the nomogram were determined by the concordance index (C-index) and a calibration curve, and the results were compared with four currently used ICC staging systems. Results: On multivariate analysis of the training cohort, serum CA 19-9, albumin-bilirubin grade at recurrence, time from primary resection to recurrence, tumor number at recurrence, and treatment for recurrence formed the basis of the nomogram. The calibration curve revealed good agreement between prediction by nomogram and actual observation. The C-index of our model for predicting survival was 0.791 (95% confidence interval (CI), 0.736 to 0.846), which was statistically higher than the values of the following systems: American Joint Committee on Cancer (AJCC) eighth edition (0.610), Nathan (0.582), Liver Cancer Study Group of Japan (0.613), and Okabayashi (0.600; P<0.001 for all). The findings were supported by the validation cohort. Conclusions: Compared with four currently used staging systems for ICC, our nomogram showed more promising clinical utility in improving individualized predictions of survival for postoperative recurrent ICC patients.